Observation of Omnidirectional Exchange Bias at All‐Antiferromagnetic Polycrystalline Heterointerface - Asakura, Mihiro; Higo, Tomoya; Matsuo, Takumi; Uesugi, Ryota; Nishio‐Hamane, Daisuke; Nakatsuji, Satoru (Advanced Materials, 2024)
Due to promising functionalities that may dramatically enhance spintronics performance, antiferromagnets are the subject of intensive research for developing the next‐generation active elements to replace ferromagnets. In particular, the recent experimental demonstration of tunneling magnetoresistance and electrical switching using chiral antiferromagnets has sparked expectations for the practical integration of antiferromagnetic materials into device architectures. To further develop the technology to manipulate the magnetic anisotropies in all‐antiferromagnetic devices, it is essential to realize exchange bias through the interface between antiferromagnetic multilayers. Here, the first observation on the omnidirectional exchange bias at an all‐antiferromagnetic polycrystalline heterointerface is reported. This experiment demonstrates that the interfacial energy causing the exchange bias between the chiral‐antiferromagnet Mn3Sn/collinear‐antiferromagnet MnN layers is comparable to those found at the conventional ferromagnet/antiferromagnet interface at room temperature. In sharp contrast with previous reports using ferromagnets, the magnetic field control of the unidirectional anisotropy is found to be omnidirectional due to the absence of the shape anisotropy in the antiferromagnetic multilayer. The realization of the omnidirectional exchange bias at the interface between polycrystalline antiferromagnets on amorphous templates, highly compatible with existing Si‐based devices, paves the way for developing ultra‐low power and ultra‐high speed memory devices based on antiferromagnets. An exchange bias effect at an all‐antiferromagnetic polycrystalline heterointerface is observed. The chiral antiferromagnet Mn3Sn works as the active layer, replacing conventional ferromagnets. The unidirectional magnetic anisotropy can be determined omnidirectionally due to the absence of the shape anisotropy. These findings are significant for developing various antiferromagnetic spintronic devices, including antiferromagnetic tunnel junctions, essential for ultrafast and ultra‐power‐efficient computing.